1999
DOI: 10.1080/01904169909365761
|View full text |Cite
|
Sign up to set email alerts
|

Silicon nutrition and sugarcane production: A review1

Abstract: Silicon (Si) is one of the most abundant elements found in the earth's crust, but is mostly inert and only slightly soluble. Agriculture activity tends to remove large q uantities of Si from soil. Sugarcane is known to absorb more Si than any other mineral nutrient, accumulating approximately 380 kg ha -1 of Si, in a 12-month old crop. Sugarcane (plant growth and development) responses to silicon fertilization have been documented in some areas of the world, and applications on commercial fields are routine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
219
1
16

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(254 citation statements)
references
References 73 publications
(110 reference statements)
10
219
1
16
Order By: Relevance
“…Silicon can also alleviate imbalance between zinc and phosphorus supply as well as decrease the toxic effect of aluminum in hydroponic culture in several species [3,9,44,56]. Similar applications of silicon have also been found in other cereals and dicotyledonous plants [11,25,41,48,53]. It is also reported that silicon improves nutrient balance in a wide variety of plant species [14,28,30].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Silicon can also alleviate imbalance between zinc and phosphorus supply as well as decrease the toxic effect of aluminum in hydroponic culture in several species [3,9,44,56]. Similar applications of silicon have also been found in other cereals and dicotyledonous plants [11,25,41,48,53]. It is also reported that silicon improves nutrient balance in a wide variety of plant species [14,28,30].…”
Section: Introductionmentioning
confidence: 90%
“…Rachilla of the wheat plant also produced prickle hairs, fiber cell, dendriform phytoliths and epidermal cells (Table 1). In the last few decades the procedure of phytolith counts showed a great relevance [dendriform phytoliths (32,33), rod shaped phytolith 3 (34), hairs (35), epidermal cell (36)] and rachilla prickle hairs (37) fiber cell (38), dendriform phytoliths (39) and epidermal cells (40,41) in phytolith studies and has been used by many phytolith researchers [1,46]. We have also used this procedure in a fixed observed area of the slides and after counting we observed that the highest silicified cells were present in leaf blade followed by the awn, leaf sheath, lemma, rachilla and stem (Fig.…”
Section: Transparency and Dry Ash Technique Of Phytolith Extractionmentioning
confidence: 99%
“…Among the fertility levels, the T 1 treatment which did not receive any N or Si levels recorded the highest incidence of stem borer and dead hearts as well as leaf folder as evidenced by stem borer, dead hearts and leaf folder, compared to other treatments which received both N and Si. An increase in the level of N increased the incidence of stem borer, dead hearts and leaf folder; which of course is common for rice (Savant et al, 1999). However, when N was integrated with Si, the incidence was decreased.…”
Section: Pest Incidencementioning
confidence: 99%
“…According to Savant et al (1999) the greater crop production promoted by silicates is due to its effect on plant architecture, making the leaves more erect, enhancing light gathering, which increases CO 2 absorption and reduces transpiration. Thus, silicate fertilization increases photosynthesis rate and provides greater water-use efficiency.…”
Section: Source Of Variation Dfmentioning
confidence: 99%